2006
DOI: 10.1002/chin.200627127
|View full text |Cite
|
Sign up to set email alerts
|

Benzimidazole Inhibitors of Hepatitis C Virus NS5B Polymerase: Identification of 2‐[(4‐Diarylmethoxy)phenyl]‐benzimidazole.

Abstract: benzimidazole. -Compounds (VII) inhibit subgenomic HCV RNA replication, are selective against DNA polymerases and exhibit low cytotoxicity. -(ISHIDA, T.; SUZUKI, T.; HIRASHIMA, S.; MIZUTANI, K.; YOSHIDA, A.; ANDO, I.; IKEDA, S.; ADACHI, T.; HASHIMOTO*, H.; Bioorg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 1 publication
0
43
0
Order By: Relevance
“…Ishida et al synthesized a series of 1-cycloalkyl-2-phenyl-1H-benzimidazole-5-carboxylic acid derivatives and evaluated their inhibitory activity against hepatitis C virus NS5B RNA-dependent RNA polymerase. In their study, they found that diaryl methoxy derivatives, 20 and 21, blocked the replication of subgenomic HCV-RNA in the replicon cells (Ishida et al, 2006).…”
Section: Benzimidazoles As Antihepatitic Agentsmentioning
confidence: 98%
“…Ishida et al synthesized a series of 1-cycloalkyl-2-phenyl-1H-benzimidazole-5-carboxylic acid derivatives and evaluated their inhibitory activity against hepatitis C virus NS5B RNA-dependent RNA polymerase. In their study, they found that diaryl methoxy derivatives, 20 and 21, blocked the replication of subgenomic HCV-RNA in the replicon cells (Ishida et al, 2006).…”
Section: Benzimidazoles As Antihepatitic Agentsmentioning
confidence: 98%
“…Thus, focus was diverted at neutralizing the -carboxyl group by conversion to -CONH 2 resulted in compound 9 (IC 50 = 0.22 μM, EC 50 = 8 μM) [29]. Further improvement in enzymatic and replicon activity was achieved by replacement of - Ishida et al, [30] screened a collection of compounds from Japan Tobacco to identify potential NS5B (genotype 1b) inhibitors. Optimization of N 1 -cyclohexyl-benzi-midazole-5-carboxylic acid, an initial hit, at the 2-position led to the identification of compound 11 (genotype 1b IC 50 = 0.27 μM, replicon EC 50 = 1.1 μM, genotype 1a IC 50 = 0.80 μM).…”
Section: Nnis Binding To the Allosteric Pocketmentioning
confidence: 99%
“…Benzimidazoles such as 67a,b [137] or 68 [138] were found by scientists at Japan Tobacco (JT) and Boehringer Ingelheim (BI) as screening hits of their proprietary compound collections (Fig. 18).…”
Section: Upper Thumb Domain (Nni Site I)mentioning
confidence: 99%
“…Initial SAR on the benzimidazole series revealed that the cyclohexyl substituent is the optimal residue at N1 of the benzimidazole and that the minimum core required for activity is a benzimidazole such as 69 decorated with a cylohexyl substituent, an aryl group at the C2-position and a carboxylate at C5 [137,138].…”
Section: Upper Thumb Domain (Nni Site I)mentioning
confidence: 99%